(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
The process of introducing digital technologies is having a significant impact on human resource management. This article analyzes the challenges of training and skills development in the process of digital transformation. Digital technologies, including artificial intelligence and automation, play an important role in modernizing and improving the efficiency of human resource management. However, there are obstacles such as a shortage of qualified personnel, problems in the education system, and low levels of digital literacy. The article also provides suggestions for developing digital skills and updating education systems, which will help organizations succeed in the process of digital transformation.